PENGARUH MUTU PELAYANAN DAN FUNGSI INDEPENDEN PETUGAS PUSKESMAS TERHADAP PENINGKATAN KUALITAS KEPERAWATAN DI PUSKESMAS MAUK KABUPATEN TANGERANG - Kustirahayu Kustirahayu; Bayu Imanuddin (Nusantara Hasana Berdikari, 2022)
Public service is the task of public bodies carried out by government organizations, both at the center, territory, and state-owned enterprises (BUMN). The type of public service that is completed by public authorities is through the fulfillment of public health needs. Indonesia is a country where this development must be followed through high quality public health services. The type of public service facility coordinated by the public authority is the puskesmas. The purpose of the study was to find out whether there was a relationship between the Quality of Public Health Care Services to Improving the Quality of Nursing at the Mauk Health Center and to find out how the relationship between the Independent Functions of the Health Center Officers towards the Improvement of Nursing Quality at the Puskesmas. The research method is Cross-Sectional. Sampling was carried out by purposive sampling based on data from the Mauk Health Center, Tangerang Regency in 2021, so that 65 respondents were obtained. The data analysis technique used is the Chi square test using SPSS 22. There is a relationship between service quality and improving the quality of nursing at the Puskesmas. The results of the chi-square statistical test of the relationship of the independent function of puskesmas officers (Variable X2) to improving the quality of nursing at the Mauk Health Center (Variable Y) obtained p value = 0.000 meaning p value alpha (0.005), so it can be concluded that the null hypothesis (Ho) is rejected and The alternative hypothesis (Ha) is accepted, the conclusion is that there is a relationship between service quality and improving the quality of nursing at the Puskesmas.